Fostering Adaptive and Intelligent Learning Management Systems in Education 4.0: A Novel Framework for Implementation and Assessment - Victor Juan Pratana; Robinson Situmorang; Cecep Kustandi; Richardus Eko Indrajit (Utilitas Mathematica, 2025)
The advent of Industry 4.0 and Education 4.0 presents new opportunities and challenges in how learning processes are managed, delivered, and evaluated. Learning Management Systems (LMSs) have evolved into adaptive, data-driven, and learner-centered platforms capable of supporting diverse educational settings. This study proposes a novel framework for integrating adaptive user interfaces, blockchain technologies, machine-learning-driven analytics, and cloud-based architectures into a single LMS ecosystem to address pressing issues of security, personalization, and scalability. We conduct an extensive literature review on LMS deployments across various Education 4.0 contexts, including Islamic higher education, technologically oriented faculties, and vocational programs. Through a comparative analysis of existing solutions, we identify critical factors contributing to successful Education 4.0 implementation particularly teacher development, digital accessibility, and knowledge management. Based on these insights, we develop and validate an Adaptive and Intelligent LMS Framework (AILF) that merges cutting-edge Industry 4.0 paradigms such as blockchain-based record-keeping, real-time analytics pipelines, and AI-driven recommendation engines while ensuring open access, traceability, and data privacy. A pilot test in a medium-scale higher education environment suggests significant improvements in student engagement, data security, and teaching efficacy. We conclude that the synergy of Industry 4.0 technologies can reshape the learning factory concept into a domain where continuous and seamless learning experiences empower learners, instructors, and administrators alike. This paper contributes an integrated perspective, bridging theoretical gaps and offering practical guidelines for further research, design, and implementation of Education 4.0-focused LMS solutions.